Applying occupational and organizational psychology theory to entrustment decision-making about trainees in health care: a conceptual model - Holzhausen, Ylva (Perspect Med Educ, 2017)
In medical contexts around the world, supervising physicians continuously decide what degree of supervision to apply as trainees carry out professional activities. Although the implications for patients can be far-reaching, little is known about how these entrustment decisions are formed. The concept of ‘Entrustable Professional Activities’ has initiated interest and valuable research on factors that may influence the entrustment decision process. The aim of the current article is to link models of entrustment developed in the fields of occupational and organizational psychology and military psychology to medical education studies that have explored the factors influencing physicians’ entrustment decisions. We provide a conceptual framework of the entrustment decision-making process, which we suggest will contribute to the understanding of how supervising physicians arrive at the decision to entrust a medical trainee with a professional activity.